2005
DOI: 10.1007/s00595-005-3061-0
|View full text |Cite
|
Sign up to set email alerts
|

Bioresorbable Hyaluronate-Carboxymethylcellulose Membrane (Seprafilm) in Surgery for Rectal Carcinoma: A Prospective Randomized Clinical Trial

Abstract: Seprafilm effectively reduced abdominal adhesions in chemoradiated patients, and had no adverse effects on the oncologic results of fully introduced adjuvant therapy. Thus, Seprafilm is a safe and effective tool for use in rectal carcinoma surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 10 publications
1
75
1
4
Order By: Relevance
“…Products that have had the most documented success in humans are the absorbable gels and films. Although the use of some agents is not without certain caveats (such as the avoidance of wrapping the product around any anastomosis, and ensuring complete hemostasis), randomized control trials have shown statistically significant benefits in their ability to reduce adhesion formation [117,118,119,120,121,122,123,124,125]. As such, the predominance of evidence would suggest that unless there are any contraindications, the surgeon should consider using hyaluronic acid/carboxymethyl membranes.…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…Products that have had the most documented success in humans are the absorbable gels and films. Although the use of some agents is not without certain caveats (such as the avoidance of wrapping the product around any anastomosis, and ensuring complete hemostasis), randomized control trials have shown statistically significant benefits in their ability to reduce adhesion formation [117,118,119,120,121,122,123,124,125]. As such, the predominance of evidence would suggest that unless there are any contraindications, the surgeon should consider using hyaluronic acid/carboxymethyl membranes.…”
Section: Methods Of Adhesion Reductionmentioning
confidence: 99%
“…Adhesions to the omentum were reduced from 79% in the control group to 39% in the Seprafi lm group. Kusunoki et al evaluated the effectiveness of Seprafi lm in preventing abdominal adhesions after radical resection of rectal carcinoma and examined whether Seprafi lm had any adverse effects in patients treated with radiotherapy and chemotherapy [ 46 ] . Sixty-two patients participated and received preoperative radiotherapy followed by a two-stage operation and 5-fl uorouracil (5-FU)-based systemic chemotherapy.…”
Section: Sheetsmentioning
confidence: 99%
“…In medical use, the effectiveness of native-type hyaluronate has been previously reported in the management of radiation dermatitis [41] [Primavera, 2006], in the prevention of postoperative adhesions in the pelvis [Kusunoki, 2005], and as antioxidant [Campo, 2008], depending on its molecular weight and concentration [Krasinski, 2009].…”
Section: Native-type Hyaluronate Moleculesmentioning
confidence: 99%